The Relationship betweem school feeding and family agriculture in the municipality of Guaraniaçu - PR - Cassol, Bruna; Mary Guimarães Nogueira, Francis (Guará Journal, 2022)
The  objective  of  this  study  was  to  verify  how  the  connection  between  school  feeding  and  family  farming  (FA)  occurred  in  the  municipality  of  Guaraniaçu,  after  the  enactment  of  Law  11.947/2009.  This  is  a  qualitative  research,  involving  a  case  study, carried out in two municipal schools, one located in the city and the other located in the rural area. The research invol-ved  bibliographical  consultations  and  field  research,  with  the  application of questionnaires and interviews with people rela-ted to family agriculture and school feeding in the municipality. The data were analyzed based on the analysis of content in the thematic modality of Minayo (2007), resulting in three final ca-tegories. It is considered the relevance of cooperativism for fa-mily farming in the municipality studied, which guaranteed in-come and work for family farmers. The insertion of FA products was important for improving the quality of the children’s food, because the characteristics of these products are natural, fresh, minimally  processed  and  respect  the  municipality’s  regionali-ty. Finally, it is considered that the school is a space conducive to the formation of healthy eating habits in children, since they spend a good part of their day at school
Keywords: Family Farming; School feeding; PNAE